A qualitative evaluation of healthy weight services in a local authority in England. (December 2018) - Kime, Nicky Helen; McKenna, Jim; Griffiths, Claire; Rivett, Martin; Gately, Paul
Objective: The purpose of this study was to evaluate the healthy weight services in one local authority in England, where obesity levels have been above the national average since 2006. Design: We conducted process and outcome evaluation using a qualitative methodology. Data were generated in focus group discussions and semi-structured interviews with clients, practitioners, healthcare professionals and volunteers. Results: A total of 91 individuals from six services participated in the evaluation. Staff competencies and empowerment outcomes were identified as areas of strength. However, despite examples of excellent practice and enthusiastic recommendations from clients, access and referral processes were areas of weakness. Conclusion: In England, local authorities have an important role to play in tackling obesity. It is crucial that they are provided with the tools to be able to implement healthy weight interventions effectively. A whole-systems approach presents a real opportunity for staff in local authorities and public health to work collaboratively and innovatively towards the same goal of continuous improvement in obesity management.